1967
DOI: 10.1017/s0021859600018621
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen and irrigation on timothy (Phleum pratense) grown for production of seed: I. Vegetative growth

Abstract: 1. Plants of S.48 timothy were established on a 1 ft square pattern for production of seed. Two series of plots, one irrigated and one not irrigated, were treated with three levels of applied nitrogen: 0 (NO), 87 (Nl) and 261 (N2) lb N per acre (0, 97·5 and 292·5 kg N/ha) per annum, for 3 years. In this, the first of two papers, only vegetative aspects of growth are considered. Since the irrigation treatment started only 2 weeks before most of the data were recorded, effects of irrigation on vegetative growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, there was no indication of a higher requirement for nitrogen where plots were irrigated, as was found in the work with cereals, and in the third year of the present work irrigation did not increase yield where nitrogen had been applied. It seems possible that the results were influenced by other factors, some of which have been previously presented and discussed (Lambert, 1967), such as the soil moisture deficit, the weight of roots present and the effect of nitrogen on the growth of the plant.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, there was no indication of a higher requirement for nitrogen where plots were irrigated, as was found in the work with cereals, and in the third year of the present work irrigation did not increase yield where nitrogen had been applied. It seems possible that the results were influenced by other factors, some of which have been previously presented and discussed (Lambert, 1967), such as the soil moisture deficit, the weight of roots present and the effect of nitrogen on the growth of the plant.…”
Section: Discussionmentioning
confidence: 93%
“…The timothy was harvested when the majority of the seed was light brown. An area of 4 drills x 7 ft (2-1 m) was used for determination of yield of seed (Lambert, 1967). Material was stored in muslin bags, subsequently threshed in a machine built at N.I.A.E.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrigation was discontinued after flowering on the basis of previous research (Lambert 1967;Cookson et al 2000). In coolseason perennial grasses, many of the studies on irrigation (Lambert 1967;Hebblethwaite 1977;Chastain et al 2014) and precipitation during anthesis (Abel and Boelt 2018) suggested that wet weather and amount and timing of precipitation could depress pollination, as well reduce yield-component development. Nitrogen as granular ammonium nitrate (340 g N kg -1 ) was spread manually on the soil surface at the appropriate rates for the subplots receiving 25, 50 and 75 kg N ha -1 on 30 October 2009 (21 days after mowing for the first crop) and 25 February 2010 (20 days after mowing for the second crop).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%